المنطق الماصدقي: تاريخه وخصائصه وتطبيقاته - محمد سيد محمد أبوالعلا (Maǧallaẗ Kulliyyaẗ Al-ādāb Ǧāmiʿaẗ Būrsaʿīd, 2022)
لم يُعرف التمييز بين حدي القضية - المفهوم والماصدق - بشکلٍ انفصالي کلٌ على حدة إلاَّ في وقتٍ متأخر؛ فکل قضية تتکون من حدين هما المفهوم والماصدق، والعلاقة بينهما عکسية کما نعلم؛ کلما زاد المفهوم قل الماصدق والعکس، لکن هذا لا يعني القول بأحدهما فقط دون الآخر، وهذا البحث يعرض في مجمله تعريف المنطق الماصدقي، وبداياته المتعارف عليها تاريخيًا، وعلاقته بالمنطق المفهومي، والفرق بين المفهومي والماصدقي، وأشهر علماء المنطق الذين يعلون من شأن الماصدق؛ فيقولون بالنزعة الماصدقية، أو ما يعرف بالمنطق الماصدقي، ولماذا الانحياز التام في بعض الفترات له على حساب منطق المفهوم، مع أن کلاهما يکمل الآخر؟، کما يعرض فيه الباحث کذلک إلى أنواع الماصدقات المختلفة، أو النزعة الماصدقية، فيبين أن منها ماصدقية صريحة، ومنها ماصدقية ضمنية، مبينًا دور بعض علماء المنطق الذين أوصوا بضرورة التخلي عن المفهومات، مع بيان خصائص المنطق الماصدقي، وأهم ثوابت ومتغيرات المنطق الماصدقي، والسياقات الماصدقية ودلالاتها، ونظرية الأنماط الماصدقية، وأثر هذه النظرة في نظريات: المجموعات، الأنماط، الميرولوجيا، ولغات البرمجة، وأبرز تطبيقات المنطق الماصدقي في برمجة المنطق الاستقرائي. Abstract The distinction between the two terms of the Proposition, the Intension and the extension, in a separatist way, was not known until a later date. This research presents, in its entirety, to the definition of the extensional logic and its historically recognized beginnings, its relationship to the Intensional logic,The difference between the intension and the extension, and the most famous logician who exalted the extensional logic, They say of the extensionalism, or what is known extensional logic, and why is the complete bias in some periods to it at the expense of the  intension logic, even though both complement the other? The researcher also presents it to the different types of extensions, and shows that some of them have explicit extensionality, and some Implicit extensionality, indicating the role of some logic scholars who recommended the need to abandon intensions, with an explanation of the characteristics of extensional logic, the most important constants and variables of extensional logic, extensional contexts and their implications, the theory of extensional types, and the impact of this view on the theories: sets, types, mereology, and programming languages. The most prominent applications of the extensional logic in the programming of inductive logic.